The Politics of Urban Space: A Sociological Study of Pavement Hawkers - Niriella, N. Chandrasiri (My University, 2012)
This paper focuses on the politics of urban space in the context of pavement hawkers of Colombo City and its suburbs. The traditional role of vending in the subsistence economy of rural areas or towns and cities has undergone structural change. Rapid urbanization, as an off-shoot of industrial, technological and commercial activity, has changed the urban scene drastically where the conflict for urban space has become a long drawn struggle of urban poor who may constitute even a half of the population of the city. As observed, in high growth profile cities, like Mumbai, Delhi, Calcutta and Colombo, vending (e.g. the sale of lottery tickets, newspapers, cloths, toys, tools, sweets, fruits and vegetables, etc.), no more remain an unnoticed activity but a major source of survival and also conflict between the city managers and city planners on the one hand, and the large number of vendors and hawkers, on the other. This conflict for urban space has to be understood through its relationship with the political economy of city. Thus, contemporary pavement hawking in high growth profile cities, is no more confined to a survival struggle of the ‘poor people’ but involves multi-actors, including local politicians, musclemen, and bureaucrats. Therefore, their struggle for a share in the urban space has to be understood in its proper perspective. The paper presents an overview of related theories in the spatial context of evolution of the city. The ecological theory is reconsidered for its over-emphasis on the role of spatial forms in the city on human relationships. However, the original Marxian perspective that the city has no other role to play than being instrumental in capital formation is also scrutinized. As observed by a few key thinkers on the urban question (like Neo-Weberians and Neo-Marxists), the political power under localized political compulsions may extend its role to tje social distribution of public goods and services which may not necessarily be within the production relationships as conceived in the class struggle paradigm. The struggle of pavement hawkers of Colombo City and its suburbs for the urban space and the role of state and bureaucracy in manipulating the needs of various interests groups, for their local political or monetary gains, amply prove this.